2017
DOI: 10.1088/1361-6595/aa963d
|View full text |Cite
|
Sign up to set email alerts
|

The role of electron induced secondary electron emission from SiO2surfaces in capacitively coupled radio frequency plasmas operated at low pressures

Abstract: The effects of electron induced secondary electron (SE) emission from SiO 2 electrodes in singlefrequency capacitively coupled plasmas (CCPs) are studied by particle-in-cell/Monte Carlo collisions (PIC/MCC) simulations in argon gas at 0.5 Pa for different voltage amplitudes. Unlike conventional simulations, we use a realistic model for the description of electron-surface interactions, which takes into account the elastic reflection and the inelastic backscattering of electrons, as well as the emission of elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
161
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(167 citation statements)
references
References 43 publications
5
161
1
Order By: Relevance
“…Other types of electron-surface processes, e.g., the emission of SEs due to electron impact, are neglected. We note that recent studies have found considerable effects of the electron induced SEs on the plasma parameters at specific discharge conditions 57,58 , i.e., at very low pressures (p ( 3 Pa) and high voltage amplitudes, for dielectric surfaces. However, in the present study, metal electrodes are assumed (compared to dielectric surfaces, the maximum of the electron induced SE yield is much lower for metal surfaces), and the discharge conditions covered here are significantly different (higher pressures, lower f tot ) compared to those in Refs.…”
Section: Simulation Methods and Discharge Conditionsmentioning
confidence: 76%
“…Other types of electron-surface processes, e.g., the emission of SEs due to electron impact, are neglected. We note that recent studies have found considerable effects of the electron induced SEs on the plasma parameters at specific discharge conditions 57,58 , i.e., at very low pressures (p ( 3 Pa) and high voltage amplitudes, for dielectric surfaces. However, in the present study, metal electrodes are assumed (compared to dielectric surfaces, the maximum of the electron induced SE yield is much lower for metal surfaces), and the discharge conditions covered here are significantly different (higher pressures, lower f tot ) compared to those in Refs.…”
Section: Simulation Methods and Discharge Conditionsmentioning
confidence: 76%
“…However, powerful models already exist for δ and ρ [21][22][23]. The implementation of δ in PIC/MCC simulations and its effects on the calculated discharge characteristics have already been studied for SiO 2 boundary surfaces [24,25]. Other electron ejection processes from surfaces by fast neutrals, metastable atoms and VUV photons are also suggested to be important [13,26].…”
Section: Introductionmentioning
confidence: 99%
“…In many past studies concerning the electron dielectric interaction, only true SEE is taken into consideration [19,20], while this neglects the fact that not all incident electrons can penetrate the dielectric surface. The recent study by Horváth et al indicated that electron reflection/backscattering can be remarkable when incident electrons have relatively low energy [29]. A similar algorithm was also employed in previous Hall Thruster simulation code EDIPIC compiled by Sydorenko et al [39].…”
Section: Theory and Model Set-upmentioning
confidence: 99%
“…Pierron et al [27] have proved that the SEY of the grooved surface greatly reduces. Swanson et al obtained similar results but with a different surface structure [28–30]. Meanwhile theoretical results, such as the saturated charge density of SSEE stage and the relation between the charge density and the flashover voltage, were also studied by Pillai and Hackam [31].…”
Section: Introductionmentioning
confidence: 98%